Structure and Distribution of Macrobenthos Community in Code River, Yogyakarta, Indonesia - Ratih Ida Adharini; Putri Latifa Arumsari (Indonesian Society of Limnology, 2021)
This research aimed to explore the community structure of macrobenthos in Code River, Yogyakarta. This research was conducted during December 2019-January 2020 in Code River, Yogyakarta. Data was taken 4 times in 6 stations. Macrobenthos was taken using a Surber net with a size of 30 x 30 cm and sampling at 5 spots in each station. Data analysis consisted of density, diversity index, dominance index, and evenness index. Water quality data consisted of water temperature, flow velocity, water depth, water pH, dissolved oxygen, and organic matter. The results showed that the density of macrobenthos ranged from 54-172 ind/m2. Our results showed that Code River has moderate diversity based on the Shannon-Wiener diversity index. Sulcospira testudinaria is the most dominant species in Code River. The evenness index showed high except at station 2 which was categorized as moderate. Code River has pretty good water quality, but stations 3, 4, and 5 which are located in the city area, it has a high organic matter content.